Assistive form filling technique for the blind - Cheung, Kian Kok (Universiti Malaysia Sarawak (UNIMAS), 2014)
There are many assistive technologies for blind users in web accessibility. Currently, screen reader is the most popular assistive technology used by blind users. The screen reader is a computer software that can interact with the user and read text aloud. It is ideal for blind users who wish to read news and email. However, there are several difficulties that blind users encounter when using screen reader to fill online forms. Most of the time, blind users seek help from the sighted to assist them in form filling. Although there are assistive technologies available for blind users, but they are not adequate enough. Poorly designed web forms only make things worse for blind users. Moreover, screen readers are not built to detect errors of any kind during process of data input. Therefore, the assistive VIOF technique for the blind, which is known as Verify Instead Of Filling is proposed to enable a faster, more reliable and friendlier form filling process. VIOF helps blind users to extract, fill and verify web forms. Furthermore, VIOF provides better assistance and accessibility to blind users in form filling. Comparative testing of VIOF and screen reader performance has been conducted. The result shows that VIOF is helpful and well accepted by blind users.